353 FACTORS ASSOCIATED WITH ADVERSE OUTCOMES IN OLDER ADULTS DIRECTLY DISCHARGED FROM THE EMERGENCY DEPARTMENT. (25th October 2022) - Mohamed, A; Leahy, A; Gabr, A; Mannion, M; Cassarino, M; Carrol, I; Hayes, C; Peters, C; Shanahan, E; O'Connor, M; Galvin, R
Abstract: Background: Older adults attend the Emergency Department (ED) frequently. Over 40% are directly discharged from the ED. The risk of adverse outcomes is high following discharge including unplanned ED return, institutionalisation, and mortality. The purpose of this study was to highlight factors that predict these adverse outcomes. Methods: A secondary analysis was completed of SOAED (a prospective cohort study examining screening instruments to predict adverse outcomes for undifferentiated older adults attending the ED) and OPTIMEND (randomised control trial examining the effectiveness of an intervention by a team of Health and Social Care Professionals along with usual care and compared this to standard ED care alone). Inclusion criteria were adults aged 65 years and over presenting to ED at a University Teaching Hospital with medical complaints and a Manchester Triage System category 2–5. Results: Three-hundred and nine patients were discharged directly from ED (mean age 80 years; 58% female). 96 patients re-attended ED within 6 months. 66 patients were re-hospitalised within 6 months. 16 patients died within six months of discharge. 63% of the discharged patients screened positive for frailty measured by PRISMA-7 (3 or more). Relative risk ratio analysis confirmed that the risk of revisiting a hospital was 1.241 times for patients that scored frail compared to those who scored not frail. The risk of mortality was 1.075 times for patients that scored frail compared to those who scored not frail. The risk of being admitted to a nursing home was 1.146 times for patients that scored frail compared to those who scored not frail. Conclusion: Older people have a high ED re-attendance rate of 31% after an index visit. Frailty (scored on PRISMA-7) is a significant predictor of adverse outcomes. Focused screening and intervention for frail patients who attend the ED should be a priority.